Follow the Money: Quantifying Domestic Effects of Foreign Bank Shocks in the Great Recession - Cetorelli, Nicola; Goldberg, Linda S (American Economic Review, 2012)
Foreign banks pulled significant funding from their US branches during the Great Recession. We estimate that the average-sized branch experienced a twelve percent net internal fund “withdrawal,” with the fund transfer disproportionately bigger for larger branches. This internal shock to the balance sheet of US branches of foreign banks had sizable effects on their lending. On average, for each dollar of funds transferred internally to the parent, branches decreased lending supply by about forty to fifty cents. However, the extent of the lending effects was very different across branches depending on their pre-crisis modes of operation in the United States.